2004
DOI: 10.2337/diabetes.53.8.2101
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Loss of Proteoglycans and Lack of Albuminuria in Protein Kinase C-α—Deficient Diabetic Mice

Abstract: Activation of protein kinase C (PKC) isoforms has been implicated in the pathogenesis of diabetic nephropathy. We showed earlier that PKC-␣ is activated in the kidneys of hyperglycemic animals. We now used PKC-␣ ؊/؊ mice to test the hypothesis that this PKC isoform mediates streptozotocin-induced diabetic nephropathy. We observed that renal and glomerular hypertrophy was similar in diabetic wild-type and PKC-␣ ؊/؊ mice. However, the development of albuminuria was almost absent in the diabetic PKC-␣ ؊/؊ mice. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
127
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(144 citation statements)
references
References 55 publications
13
127
1
1
Order By: Relevance
“…Diabetic PKC-␣ knockout mice had comparable upregulation of glomerular TGF-␤ as their wild-type counterparts, whereas TGF-␤ upregulation was abrogated in diabetic PKC-␤ knockouts. 10,11,41 The TGF-␤1 promoter has regulatory binding sites for the transcription factor AP-1. 13 AP-1 is activated by HG in MCs and in diabetic kidneys.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diabetic PKC-␣ knockout mice had comparable upregulation of glomerular TGF-␤ as their wild-type counterparts, whereas TGF-␤ upregulation was abrogated in diabetic PKC-␤ knockouts. 10,11,41 The TGF-␤1 promoter has regulatory binding sites for the transcription factor AP-1. 13 AP-1 is activated by HG in MCs and in diabetic kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…PI3K/Akt signaling mediated glucose-induced hypertrophy in MC and tubular epithelia. 15,48 Glomerular hypertrophy is attenuated in diabetic PKC-␤ null mice, 10,11 whereas PKC␣ deletion did not affect this parameter, 41 thus supporting a role for PKC-␤1/Akt signaling in mediating cell and organ size. Although a significant decrease in renal hypertrophy was not observed in type 1 diabetic rats treated with ruboxistaurin, glomerular hypertrophy was not specifically assessed.…”
Section: Hg Versus Others) (D) Ap-1 Activity Was Also Prevented Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Other pathways in addition to PKC-␤ may also mediate some of these processes. Recently, it was shown that hyperglycemia-induced downregulation of the negatively charged basement membrane heparin sulfate proteoglycan perlecan was prevented in mice lacking PKC-␣, which also had a reduction in diabetes-associated albuminuria (44). Our data on PKC activity in renal cortex and activation of the ␣ isoform in the PKC-␤ Ϫ/Ϫ mice would be consistent with the view that activation of PKC-␣ may also contribute to albuminuria observed in diabetes despite it not being involved in causing extracellular matrix accumulation and renal hypertrophy.…”
Section: Diabetes Vol 55 November 2006mentioning
confidence: 99%
“…Genetic studies in the mouse have indicated that particular PKC isoforms are essential in a number of specific contexts [67][68][69][70][71][72][73][74][75]. As would be expected given their multiple and specific properties in vitro, the deletion of individual PKC isoform pathways leads to distinct phenotypes in KO mice [28,[76][77][78][79]. Surprisingly, in a given cascade, KOs of the various isoforms assign specific non-redundant biological functions to each isoform, which were not compensated for by the others [28,[76][77][78][79].…”
Section: Retinopathy the Overall Results For Two Studies Of Diabetic Rmentioning
confidence: 99%